2002
DOI: 10.1002/app.10652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamp cycling on conversion and stress development in ultraviolet‐cured acrylate coatings

Abstract: ABSTRACT:In radiation-cured acrylate coatings, a high conversion of monomer is generally desired to improve hardness, prevent further slow reaction upon aging, and avoid surface toxicity; however, shrinkage and, consequently, stress in coatings tend to increase with conversion. One route to achieve high conversion while maintaining low coating stress is to promote stress relaxation. In this study, acrylate coatings were cured with a UV lamp that was cycled on and off, varying the period from 2 to 60 min while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 150 publications
(147 reference statements)
1
18
0
Order By: Relevance
“…Fig. 8 demonstrates that the large majority of the overall stress is developed in the final stage of polymerization when the modulus is high, which is consistent with the general observations in the polymerization of other kinds of (meth)acrylate [13,44,45].…”
Section: Shrinkage Stress Developmentsupporting
confidence: 88%
See 1 more Smart Citation
“…Fig. 8 demonstrates that the large majority of the overall stress is developed in the final stage of polymerization when the modulus is high, which is consistent with the general observations in the polymerization of other kinds of (meth)acrylate [13,44,45].…”
Section: Shrinkage Stress Developmentsupporting
confidence: 88%
“…Stress increase is insignificant until 40%, 50%, 70% and 80% conversion for E0, E3, E10 and E30, respectively. Wen et al reported in neat oligoethylene glycol multi-(meth)acrylate systems, significant stress develops only at high conversions, which are much higher than gelation conversion and R max p conversion [44]. Their results show that the stress developed in the gelled state is small because of low modulus and fast relaxation.…”
Section: Shrinkage Stress Developmentmentioning
confidence: 80%
“…[40,41] In the standard photoresists SU-8 stresses are around 20 MPa [42] before and up to 75 MPa [43] after postexposure bake. A further advantage for the production of stable nano-patterns is the reduced CTE (Table 1) for better thermal stability.…”
Section: Internal Stressmentioning
confidence: 99%
“…Processing and microstructure development of ceramic and polymer coating prepared by depositing a solution or dispersion have been of interest in last few years [2,3]. Nano-sized antimony-doped tin oxide particles and poly(n-butyl methacrylate) lattices were combined to construct transparent conductive coating and a reduction in the percolation threshold was observed in the latex-based matrix [4].…”
Section: Introductionmentioning
confidence: 99%